Kraška kutja, izgubljeni kamen kamnitih zatočišč Evrope - Juvanec, Borut (Etnolog. Nova vrsta (Ljubljana), 1996)
In his article the author ties redimentary stone structures into a system which extends from Malta to Scotland and from Catalonia to Istria and Dalmatia. The Slovene Karst variety of stone shelter - called kutja or hiška -thus completes a horizontal arch spanning the nothern part of the Mediterranean.
Keywords: Juvanec, Borut, 1944-; kutja; Slovenia; Slovenija; ethnology; etnologija; karst; Kras; architecture; arhitektura